The Relationship Between Team Management and Enhancing Organizational Resilience in the Municipalities of Northern Gaza Amid the Israeli War (2023–2025) - Elmasry, Mohana Hasen Ebrahim (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to examine the relationship between team management and the enhancement of organizational resilience in the municipalities of Northern Gaza during the Israeli war (2023–2025). The study employed a descriptive-analytical approach and utilized a questionnaire to collect data from emergency committees in the municipalities of Northern Gaza (Jabalia Al-Nazla, Beit Lahia, and Beit Hanoun), comprising a total of 46 employees.The study found that the municipalities of Northern Gaza demonstrate a high level of team management, including team interaction, team cohesion, and team commitment. However, the municipalities face clear challenges and difficulties that hinder their organizational resilience, which was found to be at a moderate level. Additionally, the study revealed a statistically significant positive relationship between team management (team interaction, cohesion, and commitment) and the enhancement of organizational resilience in these municipalities.The study recommended that the Palestinian government and official institutions adopt a comprehensive national policy to strengthen the resilience of municipalities amid the ongoing conflict. This should include clear mechanisms for coordination between municipalities and relevant ministries. Moreover, it called on donor agencies and international organizations (e.g., UNDP, OCHA, GIZ) to implement institutional capacity-building projects that focus on supporting organizational resilience and developing decentralized decision-making models that enable rapid response and effective distribution of responsibilities during emergencies.
Keywords: Team Management; Organizational Resilience; Municipalities of Northern Gaza